Miejsce Księgi Hioba w kanonie biblijnym - Tronina, Antoni (The Biblical Annals, 2017)
The author touches upon the question of the canonical interpretation of the Bible as instanced by the Book of Job. First, he discusses the place of the Book of Job in the Jewish and Christian canons. In the end, he presents some hermeneutic implications that result from that fact that Job has been placed in the third sector of canon (Ketubim, Hagiographa), usually in the first place. This indicates that there is a need to read according to the key of biblical wisdom (hokma), rather than in the historical aspect.